Effect of sulphur levels in the production, chemical composition and digestibility of hydroponic green fodder barley (Hordeum vulgare L) - Quispe Cusi, A. (2016)
This study aimed to evaluate the effect of sulfur levels as additive in the production, chemical composition and digestibility of hydroponic green fodder barley. Four levels of S were used: 0, 20, 30 and 40 ppm and harvest was done at 18 days. A completely random design was used with five repetitions. Biomass production (PB) and the height of stem (AT) were 34.9±0.5 kg/m2 and 14.61±1.38 cm, respectively, having a lineal response for PB (Y=5.33+0.67X) and AT (Y=10.10+1.80X). The 0 S level showed higher crude protein (CP) content and nitrogen-free extract: 12.95±4.21% and 55.19±3.95% respectively; the 30 ppm level showed higher content of crude fibre (CF) to the raw fiber and neutral detergent fiber (NDF): 23.61±3.65% and 65.95±4.15% respectively; and the 40 ppm level showed higher content of ether extract (EE) and ash: 3.88±3.15% and 4.61±2.98%, respectively. The apparent digestibility of CF and EE were significantly affected by sulfur levels.